Euphorias in Gender, Sex and Sexuality Variations Positive Experiences - Jones, Tiffany (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This Open Access book uses the concept of 'euphoria' to investigate when, why and how marginal gender, sex and sexuality groups have positive experiences of their diverse variations even within repressive and disordering contexts. Drawing on data from multiple online surveys including a study of 2,407 LGBTQ+ people and a study of 272 people with intersex variations, it names and offers a new ecological framework for understanding participants' influences on and barriers to euphorias, asserting the subversive possibilities of being euphorically queer, as opposed to euphoric and queer. The author argues that it is the particularities of negative internal, socio-cultural and institutional contexts for a marginal group or groups that contributes towards the possibilities that shape their potential euphoric feelings and experiences. Ultimately, she calls for a more expansive focus in gender and sexuality studies to show the complex effects of dysphoria and repression on the possibilities of pleasure and joy. This book will be of interest to scholars across Gender, Sexuality and Queer Studies.